A review of pharmaceutical policies in response to economic crises and sanctions - Mehrnaz Kheirandish; Arash Rashidian; Abbas Kebriaeezade; Abdol Majid Cheraghali; Fatemeh Soleymani (Wolters Kluwer Medknow Publications, 2015)
An economic crisis has been defined as a situation in which the scale of a country's economy becomes smaller in a period of time. Economic crises happen for various reasons, including economic sanctions. Economic crises in a country may affect national priorities for investment and expenditure and reduce available resources, and hence may affect the health care sector including access to medicines. We reviewed the pharmaceutical policies that the countries adopted in order to mitigate the potential negative effects on access to medicines. We reviewed published reports and articles after conducting a comprehensive search of the PubMed and the Google Scholar. After extracting relevant data from the identified articles, we used the World Health Organization (WHO) access to medicines framework as a guide for the categorization of the policies. We identified a total of 40 studies, of which 10 reported the national pharmaceutical policies adopted to reduce the negative impacts of economic crises on access to medicines in high-income and middle-income countries. We identified 89 policies adopted in the 11 countries and categorized them into 12 distinct policy directions. Most of the policies focused on financial aspects of the pharmaceutical sector. In some cases, countries adopted policies that potentially had negative effects on access to medicines. Only Italy had adopted policies encompassing all four accesses to medicine factors recommended by the WHO. While the countries have adopted many seemingly effective policies, little evidence exists on the effectiveness of these policies to improve access to medicines at a time of an economic crisis.